REORDERING DIPLOMACY AMIDST THE COVID-19; AFRICA AND THE REST OF THE WORLD - Adetiba, Toyin (Journal of Social Political Sciences, 2021)
The Covid-19 pandemic will certainly affect the direction and development of new human civilisation as it marks the history of the 21st century like the Spanish flu of 1918. Although Covid-19 has brought the world to its knees but has at the same time united the seemingly different world. With Covid-19 the world has had to adapt to a new kind of normal, and as a global phenomenon, the pandemic has for once and diplomatically re-ordered the entire world where every country has had to choose which side of the diplomatic coin it belongs. The virus has potentially grouped countries of the world into the rich, with strong and more efficient health and political institutions, scientific knowledge and innovation, and the poor, whose economy cannot adequately support its citizens. The Covid-19 has challenged the modern diplomacy, forcing every state to consider the pandemic as a top priority owing to its crippling impact on the global economy. Amidst the political tension in Africa between groups and individual needs vis-Ã -vis state and international requirements, will Africa be able to diplomatically navigate its way through the Covid-19 â€œworldâ€? This work uses the lens of innovative diplomacy, thematic content analysis, and a critical discourse approach to unpack the relevance of innovative diplomacy to Africa amidst the pandemic and conclude that Africa need to understand the contemporary diplomatic environment vis-Ã -vis the importance of innovation diplomacy.